Potensi Dan Sebaran Jenis Pidada (Sonneratia caseolaris) Berdasarkan Jenis Tanah di Tahura Ngurah Rai - Bali - Anesa Ronavia; I Wayan Restu; I Ketut Wijanegara (Journal of Marine and Aquatic Sciences, 2020)
Ngurah Rai Forest Park Bali is a mangrove forest area located along Benoa Bay. Tahura Ngurah Rai area was found in more than 10 types of mangroves, one of which was the caseolaris Sonneratia. This study aims to determine the potential and distribution of caseolaris Sonneratia based on soil type, and determine the type of substrate in the caseolaris Sonneratia distribution. The method is observational by sampling plots for tree stand categories and pole categories five station areas. Water parameters analyzed were temperature, dissolved oxygen, salinity, and pH. The soil parameters analyzed were soil pH, organic C, Nitrogen, Phosphorus, potassium, and water content. The results showed that the density of caseolaris Sonneratia trees at each station varied where the highest at station V (Nusa Dua) at 1,397 ind / ha and the lowest at station II (Suwung Kauh) with density of 177 ind / ha. Specific density values five stations fall into criteria. The type closure that entered the criteria of lack / damage is found at stations I, II, III, and IV, while for the category of very dense (good) at station V. The most pattern is the distribution pattern "clustered" (ind> 1). The range of physics-chemical parameters the waters in Tahura Ngurah Rai the highest temperature 30.33 oC and the lowest 28.36 oC , the highest salinity 25 ppm and the lowest 11 ppm, the highest dissolved oxygen 6.16 mg / L and the lowest 6.2 mg / L, the highest pH values are 8 and lowest 7.